The Effectiveness of Hybrid Beamforming in Enhancing the Performance of NOMA-mmWave and Massive MIMO Systems - Oubassghir Mourtada; Boulouird Mohamed (ITM Web of Conferences)
As wireless networks evolve, the integration of Non-Orthogonal Multiple Access (NOMA), Massive Multiple Input Multiple Output (mMIMO), and millimeter wave (mmWave) technologies emerges as an effective approach to drive this advancement. This integration boosts both spectral efficiency (SE) and energy efficiency (EE), ensuring more reliable, faster, and energy-efficient communication systems for wireless communications, including 5G and beyond. This study aims to examine the performance of this integration in terms of SE and EE by employing a system model featuring a single base station equipped with multiple antennas that generate distinct beams serving multiple users using max-min fairness power allocation. We compare the achieved SE and EE with the Orthogonal Multiple Access (OMA) technologies used in previous generations. Furthermore, we explore the effect of using hybrid and full digital beamforming architectures on energy consumption. Through this analysis, we aim to demonstrate how employing NOMA-mMIMO and mmWave integration with a hybrid structure can achieve high SE and low energy consumption.